Formononetin Administration Ameliorates Dextran Sulfate Sodium-Induced Acute Colitis by Inhibiting NLRP3 Inflammasome Signaling Pathway - Wu, Dacheng; Wu, Keyan; Zhu, Qingtian; Xiao, Weiming; Shan, Qing; Yan, Zhigang; Wu, Jian; Deng, Bin; Xue, Yan; Gong, Weijuan; Lu, Guotao; Ding, Yanbing (Mediators of Inflammation, 2018)
Formononetin is a kind of isoflavone compound and has been reported to possess anti-inflammatory properties. In this present study, we aimed to explore the protective effects of formononetin on dextran sulfate sodium- (DSS-) induced acute colitis. By intraperitoneal injection of formononetin in mice, the disease severity of colitis was attenuated in a dose-dependent manner, mainly manifesting as relieved clinical symptoms of colitis, mitigated colonic epithelial cell injury, and upregulations of colonic tight junction proteins levels (ZO-1, claudin-1, and occludin). Meanwhile, our study found that formononetin significantly prevented acute injury of colonic cells induced by TNF-α in vitro, specifically manifesting as the increased expressions of colonic tight junction proteins (ZO-1, claudin-1, and occludin). In addition, the result showed that formononetin could reduce the NLRP3 pathway protein levels (NLRP3, ASC, IL-1β) in vivo and vitro, and MCC950, the NLRP3 specific inhibitor, could alleviate the DSS-induced mice acute colitis. Furthermore, in the foundation of administrating MCC950 to inhibit activation of NLRP3 inflammasome, we failed to observe the protective effects of formononetin on acute colitis in mice. Collectively, our study for the first time confirmed the protective effects of formononetin on DSS-induced acute colitis via inhibiting the NLRP3 inflammasome pathway activation.